Comparative Study of Visual Programming Procedures for 3D Concrete Printing of Different Geometric Shapes - Forcael, Eric; Alucema, Elena; Burkart, Adolfo; García-Alvarado, Rodrigo; Sepúlveda-Morales, Javier; Martínez, Eder (Revista Ingeniería de Construcción, 2024)
3D concrete printing offers significant advantages over traditional construction methods, including eliminating formwork and facilitating the production of complex designs. However, challenges remain in optimizing the computational design processes for printing different geometries. This research presents a comparative analysis of visual programming routines used in 3D concrete printing for sixteen different geometries, focusing on the printing times of a robotic arm. The results show that although some geometries are printed faster than others, the differences in printing times are not significant. These findings suggest that architects, engineers, and constructors can confidently pursue increasingly complex shapes without being constrained by geometric complexity, thereby expanding the creative potential of 3D concrete printing.